Islamic unit trust investment decision making: An empirical study of Muslim investors in Malaysia / Noraini Yusuff - Noraini , Yusuff (2018)
Investment decision making process is an important concept within consumer behaviour and behavioural finance discipline. The term ‘investment decision making’ has come to the attention of the general public for the past 50 years that acts as a guide in making decisions related to business investment. Moreover, investment decision making has received considerable attention from scholars and investment managers, but its complex concepts are yet to be understood and explored especially in Shariah perspective. Hence, the main purpose of this study is to investigate the determinants of investment decision making in Islamic unit trust (IUT) among Muslim investors in Malaysia. More importantly, this study also investigated several factors which include demographic characteristics, Islamic financial literacy (IFL), information sources (IS), religiosity (RE), and investment risk (IR) which can influence the Muslim investors in Islamic unit trust investment decision making (IUTID). In addition, this study also examined the role of product knowledge (PK) in the model of IUTID. The novelty of this study was to determine the mediating effects (intervening effects) of product knowledge on the relationship between Islamic financial literacy and information sources with IUTID. The second uniqueness of this study was to identify the moderation effects (interaction effects) of product knowledge on the relationship between information sources and religiosity with IUTID. The present study adopted the quantitative method research approach to conduct a survey using questionnaire. A total of 1000 questionnaires were distributed to Muslim investors in Islamic unit trust in Malaysia. In relation to this, descriptive analysis, Mann-Whitney U Test, Kruskal-Wallis H Test, and Partial Least Square Structural Equation Modelling (PLS-SEM) were employed for analysis purposes. The results obtained from Mann-Whitney U Test and Kruskal-Wallis H Test revealed that age and income significantly influence IUTID. Moreover, PLS-SEM results showed the positive relationship between Islamic financial literacy, information sources, religiosity, investment risk, and product knowledge with IUTID. The results are consistent with the Engel, Blackwell, and Miniard Decision Making Model. Furthermore, the PLS-SEM results showed that product knowledge partially mediates the relationship between Islamic financial literacy and information sources with IUTID. Meanwhile, the PLS-SEM results also proved the moderate relationship between information sources and religiosity towards IUTID by product knowledge. This study presented three contributions to the behavioural decision research which are described as follows: (1) the scope of the relationship between Islamic financial literacy, information sources, religiosity, and investment risk among Muslim investors considering that it is new to the Islamic context and act as additional literature in that particular area, (2) the mediation and moderation effect of product knowledge in the model of decision making, and (3) a new model in investment decision making which can be tested in other area of financial decision making.